Competition and market power in the Latin American banking sector - Rodrigo Lluberas (Inter-American Development Bank (IDB), 2025)
The functioning of the banking sector is key for economic growth. In this paper, we first gather banks' balance sheet monthly regulatory information in a consistent manner for seven Latin American countries. Second, we estimate lending markups and deposits markdowns in each country over time. Third, with the estimated markups and markdowns in the different countries we study how they relate with banks' profitability, the cost of credit, credit risk and credit supply. Finally, we explore whether there are differences in markups on lending rates and markdowns on deposit rates between international and domestic banks.
Keywords: E44; L11; L16; G21; 330; Banking; Markups; Markdowns; Market concentration; Latin America